5 Stat. at Large of Pa. 613 (J. Mitchell & H. Flanders Comm'r. 1898) - (:unkn) unknown (My University, 1759)
All persons enrolled to be armed with a musket, fuse, firelock, cutlass, bayonet or tomahawk, cartridge box, twelve shots of ball and powder. Allowed individuals to opt out. Used by the Court to show an idiomatic meaning for the term arms, ie to "carry."
Keywords: REQUIRED POSSESSION